Mitigating adverse effects of salt stress using exogenous proline in rice (Oryza sativa): Mitigating salt stress using proline in rice - Jharna, D E; Hossain , M M; Rabbi , F (Bangladesh Journal of Agriculture, 2026)
Salt stress is certainly one of the most serious environmental factors limiting the productivity of rice plants, particularly in the coastal and salt-affected regions of Bangladesh. The present study was undertaken to investigate the effect of exogenous proline on the morphological, physiological, and biochemical responses of two rice (Oryza sativa L.) genotypes, namely BINA dhan23 and Sadamota under salt stress conditions (6 dS m⁻ ¹). The experiment was conducted in a net-house and laboratory of the Department of Biochemistry and Molecular Biology at Patuakhali Science and Technology University. The experimental treatments consisted of four combinations: T1-control, T2-proline spraying, T3-salt stress and T4-salt stress with proline spraying. A Randomized Complete Block Design (RCBD) with three replications was used. Data on plant parameters including plant height, tiller number, panicle and grain characteristics were recorded. The physiological and biochemical traits such as proline content, chlorophyll content, total sugar, and K+/Na+ ratios were analyzed in leaves. Results revealed that salinity significantly reduced yield-contributing traits such as panicle length, grain number, grain yield, and straw yield, BINA dhan23 produced substantially higher grain yield (21.8 g pot-1) than Sadamota (5.58 g pot-1), indicating its stronger reproductive resilience under salinity. The grain yield decreased under salt stress (10.6 g pot-1) was partially recovered by proline spraying (11.4 g pot-1). Similarly salt stress reduced straw yield (26.2 g pot-1), while proline improved it under saline conditions (29.0 g pot-1). Exogenous proline further enhanced leaf proline content (up to 114.9 mg 100 g-1 fresh leaf), total sugar (9.06 mg 100 g-1), and chlorophyll (5.04 mg 100 g-1), while improving the K+/Na+ ratio (0.78 vs. 0.69 in Sadamota). The findings suggest that the combined use of salt-tolerant genotypes and foliar proline treatment offers a promising approach for enhancing rice productivity in salinity-prone areas. Further field-level validation is recommended to confirm these effects under diverse agro-ecological conditions. Bangladesh J. Agri. 2025, 50(2): 1-19